Short-Term Effects of the Use of Non-Rigid Tools for Postural Control by Adults with Intellectual Disabilities - Mauerberg-deCastro, Eliane [UNESP]; Moraes, Renato; Campbell, Debra Frances [UNESP] (Human Kinetics Publ Inc, 2012)
We tested the short-term effects of a nonrigid tool, identified as an anchor system (e.g., ropes attached to varying weights resting on the floor), on the postural stabilization of blindfolded adults with and without intellectual disabilities (ID). Participants held a pair of anchors one in each hand, under three weight conditions (250 g, 500 g and 1,000 g), while they performed a restricted balance task (standing for 30 s on a balance beam placed on top of a force platform). These conditions were called anchor practice trials. Before and after the practice trials, a condition without anchors was tested. Control practice groups, who practiced blocks of trials without anchors, included individuals with and without ID. The anchor system improved subjects' balance during the standing task, for both groups. For the control groups, the performance of successive trials in the condition without the anchor system showed no improvement in postural stability. The individuals with intellectual disability, as well as their peers without ID, used the haptic cues of nonrigid tools (i.e., the anchor system) to stabilize their posture, and the short-term stabilizing effects appeared to result from their previous use of the anchor system.
Keywords: haptic perception; postural control; non-rigid tools; anchor system; intellectual disability